Undersøgelser over Landbrugets Driftsforhold. Regnskabsresultater 1936—37. - Iversen, Karsten (Tidsskrift for Landøkonomi, 2018)
Undersøgelser over Landbrugets Driftsforhold. Regnskabsresultater 1936—37.